A two way authentication using bilinear mapping function for wireless sensor networks. (April 2017) - Ramachandran, Shyamala; Shanmugam, Valli
Abstract: The deployment of sensor networks for security and safety related environments requires securing communication primitives such as broadcast, multicast, and point to point communication. Security services are vital for ensuring the integrity, authenticity, and confidentiality of the critical information. Therefore, the authentication mechanisms are required to support these security services and to be resilient to distinct attacks. Recent research shows that two-way authentication provides better security and high energy saving for wireless sensor networks (WSN). In this work, we investigate a shared authentication protocol for WSNs using bilinear mapping function. Many one-way broadcast authentication protocol proposed such as Timed Efficient Stream Loss-Tolerant Authentication (TESLA), Bin and Balls Authentication (BiBA), etc., which cannot provide energy efficient authentication. Here, we propose a two-way authentication based on bilinear map function and used in secure group formation algorithm. The performance metrics such as message cost, computation and communication overhead are calculated.